2016
DOI: 10.1016/j.amjmed.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Pharmacogenomics into Clinical Practice: Promise vs Reality

Abstract: BACKGROUND Limited information is available regarding primary care clinicians’ response to pharmacogenomic Clinical Decision Support (PGx-CDS) alerts integrated in the electronic health record. METHODS In February 2015, 159 clinicians in the Mayo Clinic primary care practice were sent e-mail surveys to understand their perspectives on the implementation and use of pharmacogenomic testing in their clinical practice. Surveys assessed how the clinicians felt about pharmacogenomics and whether they thought elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 26 publications
3
56
0
Order By: Relevance
“…; St Sauver et al. ). Even with these systems, however, barriers to successful and efficient integration of PGx results exist.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; St Sauver et al. ). Even with these systems, however, barriers to successful and efficient integration of PGx results exist.…”
Section: Discussionmentioning
confidence: 97%
“…There are both technical and clinical barriers to the appropriate access and use of PGx results. Considerable effort has been made to implement clinical decision support (CDS) systems with automatic alerts to notify a prescribing physician when a relevant gene-drug interaction is present for a patient and educational components to assist the clinician with understanding the alerts (Arwood et al 2016;Caraballo et al 2016;Hicks et al 2016;Hoffman et al 2016;Manzi et al 2016;St Sauver et al 2016). Even with these systems, however, barriers to successful and efficient integration of PGx results exist.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, one of the challenges reported for the delivery of pharmacogenetics results is the identification of the right person to receive a recommendation as well as the various uses of information that might be made by each healthcare discipline. 14,15 Moreover, we found that the elaboration of an accurate clinical recommendation (with a clinical report and a posttest consultation when necessary), in addition to the molecular report, made the comprehension and application of the pharmacogenetics results easier for the specialists of the petitionary clinical departments, overcoming the already mentioned barriers to interpretation and application of the use of pharmacogenetics.…”
Section: N (%)mentioning
confidence: 94%
“…Scientific, financial, regulatory, ethical, and process challenges to clinical implementation of PG exist, with limited or lack of payer reimbursement prominent among them. Other specific challenges include limited education of clinicians, slow turnaround time of PG testing, inadequate electronic clinical decision support tools, ineffective integration of PG into the electronic health record (EHR), and limited or lack of cost‐effectiveness and clinical utility data in support of PG . While these barriers are a general representation of the field of clinical PG, they may not equally contribute to lack or limited practice of PG at specific institutions across the US.…”
Section: Introductionmentioning
confidence: 99%
“…Other specific challenges include limited education of clinicians, slow turnaround time of PG testing, inadequate electronic clinical decision support tools, ineffective integration of PG into the electronic health record (EHR), and limited or lack of cost-effectiveness and clinical utility data in support of PG. 2,[12][13][14][15][16][17][18] While these barriers are a general representation of the field of clinical PG, they may not equally contribute to lack or limited practice of PG at specific institutions across the US. For example, for clinicians at Vanderbilt University, electronic decision support may not be a barrier, given that they have an extensive system in place.…”
Section: Introductionmentioning
confidence: 99%